Penambahan Madu Dalam Pengenceran Sperma untuk Meningkatkan Motilitas, Fertilisasi dan Daya Tetas Telur Ikan Mas (Cyprinus carpio L) - Tumanung, Sudirman; Sinjal, Hengky J; Watung, Juliaan Ch (Universitas Sam Ratulangi, 2015)
The research intended to determine the optimal concentration of honey addition in sperm dilution to improve sperm motility, fertilization and eggs hatchability of goldfish (Cyprinus carpio). Experimental design used was a Complete Randomized Design (CRD) with four treatments each with three replications. The concentration of honey addition used for treatment were A (0 ml of honey in 100 mL of physiological NaCl), B (0,2 mL of honey in 99.8 mL of physiological NaCl), C (0.4 mL of honey in 99.6 ml of physiological NaCl), D (0.6 mL of honey in 99.4 mL of physiological NaCl). Sperm dilution containers used was 12 plastic cups and the container fertilization and hatching eggs container used was 12 brass plates.Â Spermatozoa motility observation performed immediately after dilution process. Fertilization observation was performed after 12 hours of fertilization process, and Egg Hatchability observation was performed after 72 hours of fertilization.Â The observation results showed that the addition of honey in sperm dilution contributed significant effect on spermatozoa motility, fertilization and eggs hatchability of goldfish (Cyprinus carpio). This observation showed that the addition of 0.6 ml of honey in a sperm dilution was the best treatment indicated by the average percentage of spermatozoa motility (80,00%), fertilization (84,00%) and eggs hatchability (82,33%). Â Keywords: Honey, spermatozoa motility, fertilization, eggs hatchability, Cyprinus carpio L